2007
DOI: 10.1523/jneurosci.3702-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Selective Attention to Visual Stimuli Reduces Cochlear Sensitivity in Chinchillas

Abstract: It is generally accepted that during periods of attention to specific stimuli there are changes in the neural activity of central auditory structures; however, it is controversial whether attention can modulate auditory responses at the cochlear level. Several studies performed in animals as well as in humans have attempted to find a modulation of cochlear responses during visual attention with contradictory results. Here, we have appraised cochlear sensitivity in behaving chinchillas by measuring, with a chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
146
1
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(160 citation statements)
references
References 49 publications
6
146
1
7
Order By: Relevance
“…In addition, experiments using crossmodal manipulations have demonstrated interactions between emotional and exogenous attention in the form of decreased P3 amplitude to auditory startle probes when emotionally intense visual stimuli are presented concurrently (Cuthbert, Schupp, Bradley, McManis, & Lang, 1998;Keil et al, 2007). In animal work, crossmodal interactions between different attention systems may even affect sensory processing at the level of sensory transduction (e.g., in the cochlea, see Delano, Elgueda, Hamame, & Robles, 2007). Altogether, these findings suggest that the different attention systems may initially operate relatively independently (i.e., not tap into each other's resources), but may compete and interact at later time points (e.g., at the level of the P3 component) or when different sensory modalities are integrated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, experiments using crossmodal manipulations have demonstrated interactions between emotional and exogenous attention in the form of decreased P3 amplitude to auditory startle probes when emotionally intense visual stimuli are presented concurrently (Cuthbert, Schupp, Bradley, McManis, & Lang, 1998;Keil et al, 2007). In animal work, crossmodal interactions between different attention systems may even affect sensory processing at the level of sensory transduction (e.g., in the cochlea, see Delano, Elgueda, Hamame, & Robles, 2007). Altogether, these findings suggest that the different attention systems may initially operate relatively independently (i.e., not tap into each other's resources), but may compete and interact at later time points (e.g., at the level of the P3 component) or when different sensory modalities are integrated.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the observed increase in MT cells inhibitory responses during the discrimination task may arise from the activation of the piriform cortex-OB circuit. It cannot be rule out, however, that because both PE and TA tasks required previous extensive learning, increased inhibition would not reflect learning but other cognitive process, such as attention, which would reflect as a top down modulation of lower level structures (Delano et al 2007;Reynolds and Desimone 1999).…”
Section: Task Dependency Of Neuronal Responsesmentioning
confidence: 99%
“…In other studies, Hocherman et al (Hocherman et al, 1981;Hocherman and Yirmiya, 1990) showed that responses of auditory cortical neurons as well as thalamic neurons in In line with the notion that attention may be able to influence early stages of auditory sensory pathway, several early study in cats (Hernandez-Peon et al, 1956;Oatman, 1971Oatman, , 1976Oatman, 1988) and a recent study in chinchillas (Delano et al, 2007) showed that visual attention during a visual discrimination task can significantly decrease cochlear sensitivity, measured by sound-evoked auditory-nerve compound action potentials and cochlear microphonics, and cochlea nucleus responses. In contrast, when the animal is performing an auditory discrimination task, little effect on the early auditory processing pathway was observed.…”
Section: Auditory Attention Studies In Animalsmentioning
confidence: 79%